A Study on Mother-daughter Relationships Analyzed from the Perspective of Feminism: Focusing on K-Drama The Glory - Liu, Qiannan (Transactions on Social Science, Education and Humanities Research, 2024)
As feminism spreads from western countries to Asia, the voices of women have been heard all over the world. There is also a great deal of literary works created by women and the female roles in some works attract East Asian scholars to analyze from the perspective of feminism. Focusing on the popular Netflix drama The Glory in 2023, written by Kim Eun-sook, this study analyzed images and relationships of two mother-daughter pairs. It also discussed social problems hidden in such mother-daughter relationships, thus gaining a more explicit understanding of the author’s way of character description from the perspective of feminism. In other words, there is the opposite mother-daughter relationship caused by social problems like the first pair and a complete mutual-aid relationship caused by social problems like the second pair. This study is expected to be conducive to the establishment of benign mother-daughter relationships in real life, propose some suggestions for the depiction of mother-daughter relationships and innovation of women’s images in future literary works, and trigger authors’ reflection on the balance between commercial value and conceptual expression of scripts.